Synthesis of Nonplanar Push–Pull Chromophores with Various Heterocyclic Moieties via [2 + 2] Cycloaddition-Retroelectrocyclization Reaction - Chen, Xu; Michinobu, Tsuyoshi (Journal of organic chemistry, 2025)
A series of 1,1,4,4-tetracyanobuta-1,3-diene (TCBD) derivatives with various heterocyclic moieties, including pyridine, carbazole, indole, and benzothiadiazole, was newly synthesized through a [2 + 2] cycloaddition-retroelectrocyclization reaction. Symmetric electron-rich 1,3-butadiynes with end-capped heterocyclic substituents were reacted with tetracyanoethylene (TCNE), yielding the target TCBD products in 60–80% yields under ambient or mild heating conditions. The thermal stability and optical and electrochemical properties of both 1,3-butadiyne precursors and the corresponding TCBD derivatives were investigated by using thermogravimetric analysis (TGA), UV–vis spectroscopy, and cyclic voltammetry (CV). The TCBD derivatives featured narrow bandgaps due to the intramolecular charge transfer interactions of push–pull chromophores. In addition, the optimized structures and frontier molecular orbitals with their energy levels were determined by density functional theory (DFT) calculations.